DIGITAL TOURISM GUIDE BOOK AS AN EFFORT TO INCREASE VISITOR SATISFACTION OF SEBATU VILLAGE, TEGALLALANG DISTRICT, GIANYAR CITY - Edvin Eka Nur Rochim; Zakiyatul Wachdaniah Taulina (Wisesa: Jurnal Pengabdian Masyarakat, 2023)
Increasing the number of tourist villages to improve the tourism sector in Indonesia needs to be balanced with the development of innovation and creativity in tourist villages. This also becomes additional work for village officials and communities to empower villages and develop tourism promotions in the Tourism Village. Limitations in developing innovation are an obstacle in tourism promotion. Therefore, a practical, easy, efficient and cheap media innovation is needed to promote Sebatu Village. This made researchers create a Digital Tourism Guide book to increase the satisfaction of visitors who visit Sebatu Village. The research method is quantitative research which uses data and numbers which are then analyzed using statistics. The subjects of this research were 40 subjects who were adjusted to criteria based on purposive sampling techniques. Data analysis and processing using SPSS. Based on the research results, it shows that there is a good influence on the level of visitor satisfaction, the majority of visitor satisfaction in the high category is 75%. Factors that influence visitor satisfaction using the Digital Tourism Guide Book are relevance of information, accuracy and reliability of information, ease and accessibility, as well as presentation of layout and visual design. Apart from that, features, such as location points that are integrated with Google Maps and QR Code, are added value.